Challenges During Review of COVID-19 Research Proposals: Experience of Faculty of Medicine, Ain Shams University Research Ethics Committee, Egypt - Marzouk, Diaa; Sharawy, Iman; Nakhla, Isabelle; El Hodhod, Mostafa; Gadallah, Hoda; El-Shalakany, Amr; Elwakil, Reda; Moussa, Mohammed M.; Ismail, Alaa; Tash, Fathy M. (Frontiers in Medicine, 2021)
The COVID-19 pandemic resulted in an overwhelming increase in research studies submitted to research ethics committees (RECs) presenting many ethical challenges. This article aims to report the challenges encountered during review of COVID-19 research and the experience of the Faculty of Medicine, Ain Shams University Research Ethics Committee (FMASU REC). From April 10, 2020, until October 13, 2020, the FMASU REC reviewed 98 COVID-19 research protocols. This article addressed the question of how to face an overwhelming amount of research submitted to the REC while applying the required ethical principles. Ethical challenges included a new accelerated mode of review, online meetings, balance of risks vs. benefits, measures to mitigate risks, co-enrolment in different studies, protection of a vulnerable COVID-19 population, accelerated decisions, online research, how to handle informed consent during the pandemic, and justification of placebo arm.